Macrophage Expression of Peroxisome Proliferator–Activated Receptor-α Reduces Atherosclerosis in Low-Density Lipoprotein Receptor–Deficient Mice - Babaev, Vladimir R.; Ishiguro, Hiroyuki; Ding, Lei; Yancey, Patricia G.; Dove, Dwayne E.; Kovacs, William J.; Semenkovich, Clay F.; Fazio, Sergio; Linton, MacRae F. (Circulation (New York, N.Y.), 2007)
Background— The peroxisome proliferator–activated receptor-α (PPARα) plays important roles in lipid metabolism, inflammation, and atherosclerosis. PPARα ligands have been shown to reduce cardiovascular events in high-risk subjects. PPARα expression by arterial cells, including macrophages, may exert local antiatherogenic effects independent of plasma lipid changes. Methods and Results— To examine the contribution of PPARα expression by bone marrow–derived cells in atherosclerosis, male and female low-density lipoprotein receptor–deficient (LDLR −/− ) mice were reconstituted with bone marrow from PPARα −/− or PPARα +/+ mice and challenged with a high-fat diet. Although serum lipids and lipoprotein profiles did not differ between the groups, the size of atherosclerotic lesions in the distal aorta of male and female PPARα −/− →LDLR −/− mice was significantly increased (44% and 46%, respectively) compared with controls. Male PPARα −/− →LDLR −/− mice also had larger (44%) atherosclerotic lesions in the proximal aorta than male PPARα +/+ →LDLR −/− mice. Peritoneal macrophages from PPARα −/− mice had increased uptake of oxidized LDL and decreased cholesterol efflux. PPARα −/− macrophages had lower levels of scavenger receptor B type I and ABCA1 protein expression and an accelerated response of nuclear factor-κB–regulated inflammatory genes. A laser capture microdissection analysis verified suppressed scavenger receptor B type I and increased nuclear factor-κB gene expression levels in vivo in atherosclerotic lesions of PPARα −/− →LDLR −/− mice compared with the lesions of control PPARα +/+ →LDLR −/− mice. Conclusions— These data demonstrate that PPARα expression by macrophages has antiatherogenic effects via modulation of cell cholesterol trafficking and inflammatory activity.